Life Insurance Companies: Determinants of Cost Efficiency and Profitability - Joseph Kwadwo Tuffour; Kenneth Ofori-Boateng; Williams Ohemeng; Jane Kabukuor Akuaku (Journal of Accounting, Business and Management (JABM), 2021)
One of the most important aspects of measuring a firm’s performance is its efficiency, through which the firm is expected to envisage effective cost reductions, thereby enhancing profitability. However, most studies conducted to explore the determinants of insurance companies’ performance has concentrated on the accounts earnings information and its components which are known to explain a small proportion of a firm’s performance. Also, studies on insurance either lump all the insurance companies together or pay more attention to non-life insurance, making it difficult to evaluate the fast growing life insurance industry in Ghana. Therefore, this study examines the efficiency of life insurance companies in Ghana utilising data from twelve life insurance companies for a period of 2013-2017. The efficiency scores were calculated using Efficiency Measurement System software. The fixed effect panel regression results show that, the significant determinants of both cost and profit functions are: price of labour, commission, gross premium and net investment income. It was also revealed that, on the average, the life insurance companies were about 71.2% cost efficient and 41.7% profit efficient. Further analysis reveals that, both profit and cost efficiency changes have statistically significant positive effect on firms’ Return on Asset. Policy-makers should institute policies that encourage these companies to operate efficiently in order to make effective capital allocation decisions to avoid collapse.